Market Function through Small Family Farms-Middleman Interaction, and Its Relation to Food Security: Evidence from Indonesia - Endar Purnawan; Yuliska; Gianluca Brunori; Natalia Gabriela Molina (International ABEC, 2021)
This research addresses the interaction between small family farms and middleman and its relation to food security. Based on a qualitative method analysis derives from farmer and intermediaries interviews, this research sheds light on four types of middleman in this area: conventional middleman, rice middleman, banana middleman, and rubber middleman. It reveals factors motivating farmers to market crops through a middleman such as best crops selling price, the quantity of the crops, a new market for subsistence crops, and tied relationship. The result indicates that each middleman's role differs depending on the interaction, where most of them are simply a way to connecting farmers to the final market to earn cash quickly. Taken together, the research findings highlight the role of each middleman, including "Bertauke" interaction, which is uniquely proven to contribute to food availability and food accessibility of the small farm households from one harvest-time to another, before recommending farmers market in order to benefit farmers and the community for better local food security.